PENGARUH INSTAGRAMABLE DAN MEDIA SOSIAL PADA KEPUTUSAN BERKUNJUNG WISATAWAN KE OBJEK WISATA KEBUN MAWAR SITUHAPA - Nurrani, Iqlima; Adiatma, Dani; Rukma, Deden Firman Syuyaman (JURNAL MASTER PARIWISATA, 2023)
This study aims to determine the effect of instagramability and social media on the decision to revisit tourists at the Situhapa Rose Garden tourist attraction. The analysis of this study uses the decision to visit as the dependent variable, by combining instagramable and social media variables as independent variables and using multiple linear regression tests as data analysis assisted by IBM SPSS software version 20.0. The data collection method used in this study was to distribute questionnaires to the research sample, namely tourists at the Rose Garden tourist attraction with a total sample of 100 respondents who were selected using a purposive sampling technique. The regression model in this study is Y = 2.709+0.954X_1+1.631X_2. This study shows that instagramable and social media variables simultaneously influence visiting decisions. Furthermore, the instagramable variable has a partial effect on the decision to visit, then the social media variable has a partial effect on the decision to visit. The ability to observe instagramable and social media variables in explaining their relationship to the visiting decision variable statistically is 74.5% (D) and the remaining 25.5% is determined by variations in other variables that are not examined. Keywords: instagramable; social media; decision to visit the situhapa rose garden tourism object